2019
DOI: 10.1029/2018jb016202
|View full text |Cite
|
Sign up to set email alerts
|

Heat and Mass Transport in a Vapor‐Dominated Hydrothermal Area in Yellowstone National Park, USA: Inferences From Magnetic, Electrical, Electromagnetic, Subsurface Temperature, and Diffuse CO2 Flux Measurements

Abstract: Vapor-dominated hydrothermal systems are characterized by localized and elevated heat and gas flux. In these systems, steam and gas ascend from a boiling water reservoir, steam condenses beneath a low-permeability cap layer, and liquid water descends, driven by gravity ("heat pipe" model). We combine magnetic, electromagnetic, and geoelectrical methods and CO 2 flux and subsurface temperature measurements in the Solfatara Plateau Thermal Area in the Yellowstone Caldera to address several fundamental questions:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 89 publications
1
17
0
Order By: Relevance
“…Along the lake's western shore are a set of prominent sinuous‐shaped, north‐south oriented, high‐amplitude, positive magnetization anomalies limited on their eastern side by a sharp gradient (violet line on Figure 7) and a negative anomaly. Such strong magnetization and sharp magnetic gradients also are observed along the leading edge of the Elephant Back flow (Qpce, northwestern corner of Figures 2a and 4a) and recently have been observed by Bouligand et al (2019) at the margin of an upper flow unit part of the Solfatara Plateau rhyolite flow. We propose that these sinuous‐shaped magnetization highs are due to vertical edges of upper flow units of the West Thumb rhyolite flow that are exposed along the western shoreline and partly buried in the lake beneath the lake sediments.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Along the lake's western shore are a set of prominent sinuous‐shaped, north‐south oriented, high‐amplitude, positive magnetization anomalies limited on their eastern side by a sharp gradient (violet line on Figure 7) and a negative anomaly. Such strong magnetization and sharp magnetic gradients also are observed along the leading edge of the Elephant Back flow (Qpce, northwestern corner of Figures 2a and 4a) and recently have been observed by Bouligand et al (2019) at the margin of an upper flow unit part of the Solfatara Plateau rhyolite flow. We propose that these sinuous‐shaped magnetization highs are due to vertical edges of upper flow units of the West Thumb rhyolite flow that are exposed along the western shoreline and partly buried in the lake beneath the lake sediments.…”
Section: Discussionsupporting
confidence: 78%
“…Such an outer ring of decreased magnetization has not been previously observed over any of the terrestrial vapor‐dominated venting areas of YNP, possibly due to the lower spatial resolution of previously available magnetic data. However, a recent high‐resolution ground magnetic survey of the on‐land, vapor‐dominated Solfatara Plateau thermal area in YNP (Bouligand et al, 2019) showed that a decrease in magnetization was restricted to the near surface and in a few areas offset from the buoyant gas and heat plume.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conductive heat transfer through the cap condenses vapor, and the heavier condensate descends in an annulus around the vapor-rich zone, forming a narrow convection cell ("heat pipe," White et al, 1971). Where fractures penetrate the low-permeability cap, some of the steam and gas are emitted to the atmosphere through fumaroles (Bouligand et al, 2019;Hurwitz & Lowenstern, 2014). This model requires some modifications in order to apply it to the sublacustrine Deep Hole hydrothermal field (Figure 3).…”
Section: Conceptual Model Of the Deep Hole Hydrothermal Systemmentioning
confidence: 99%
“…Current models for the YNP hydrothermal system are based upon geochemistry and the spatial relation between thermal features and surface geology. Permeable basal breccias 8,20 guide thermal uid ow and are thought to localize thermal features at lava ow fronts 1,2,21 . At higher elevations, the mixing of groundwater with steam and gas boiled out of deep alkaline waters create acid-sulfate pools, fumaroles and mud pots 1,14 .…”
Section: Main Textmentioning
confidence: 99%